Adiwiyata School: Can Schools Form the Character of Students Caring for Environment? - Irda Suryani; Siti Fatimah; Erna Juita (Science and Environmental Journal for Postgraduate, 2020)
This research departs from the fact that there is still much recorded about student awareness in protecting the school environment. Among them are cleanliness, which is influenced by trash and the beauty of schools. This research takes a case study at SMPN 7 Padang. This study aims to uncover and analyze the program, which was developed by the school regarding the movement to care for the environment, the obstacles faced and efforts to improve the character building of students who care about the environment. This research was conducted with a qualitative approach. This study obtained data from key informants. Using informants determined by purposive sampling. Data collection techniques using observation techniques and semi-structured interviews. The data analysis technique is done interactively through a process of data reduction, data display, verification. The results of the study show that the character building program is carried out with a program that is determined based on time, ie daily, weekly, monthly and yearly, then the adiwiyata school program has not been able to touch all students directly and be concerned about the environment. To overcome the obstacles that occur activities such as mutual cooperation and also there are punishments and rewards for student actions related to the environment.